In Vitro and In Vivo Characterization of Novel Stable Peptidic Ghrelin Analogs: Beneficial Effects in the Settings of Lipopolysaccharide-Induced Anorexia in Mice - Holubová, Martina; Blechová, Miroslava; Kákonová, Anna; Kuneš, Jaroslav; Železná, Blanka; Maletínská, Lenka (The Journal of pharmacology and experimental therapeutics, 2018)
Ghrelin, the only known orexigenic gut hormone produced primarily in the stomach, has lately gained attention as a potential treatment of anorexia and cachexia. However, its biologic stability is highly limited; therefore, a number of both peptide and nonpeptide ghrelin analogs have been synthesized. In this study, we provide in vitro and in vivo characterization of a series of novel peptide growth hormone secretagogue receptor (GHS-R1a) agonists, both under nonpathologic conditions and in the context of lipopolysaccharide (LPS)-induced anorexia. These analogs were based on our previous series modified by replacing the Ser3 with diaminopropionic acid (Dpr), the N-terminal Gly with sarcosine, and Phe4 with various noncoded amino acids. New analogs were further modified by replacing the n-octanoyl bound to Dpr3 with longer or unsaturated fatty acid residues, by incorporation of the second fatty acid residue into the molecule, or by shortening the peptide chain. These modifications preserved the ability of ghrelin analogs to bind to the membranes of cells transfected with GHS-R1a, as well as the GHS-R1a signaling activation. The selected analogs exhibited long-lasting and potent orexigenic effects after a single s.c. administration in mice. The stability of new ghrelin analogs in mice after s.c. administration was significantly higher when compared with ghrelin and [Dpr3]ghrelin, with half-lives of approximately 2 hours. A single s.c. injection of the selected ghrelin analogs in mice with LPS-induced anorexia significantly increased food intake via the activation of orexigenic pathways and normalized blood levels of proinflammatory cytokines, demonstrating the anti-inflammatory potential of the analogs.
Keywords: receptory ghrelinu; tkáňová distribuce; Protein Stability; Binding, Competitive; Male; Lipopolysaccharides; Receptors, Ghrelin; stabilita proteinů; ghrelin; přijímání potravy; Tissue Distribution; lipopolysacharidy; beta-Lactamases; signální transdukce; Amino Acid Sequence; mužské pohlaví; beta-laktamasy; Eating; Signal Transduction; kompetitivní vazba; Growth Hormone; nechutenství; Animals; zvířata; myši inbrední C57BL; sekvence aminokyselin; myši; Mice, Inbred C57BL; Ghrelin; Anorexia; Mice; růstový hormon